Four Pathways Involving Innate Immunity in the Pathogenesis of Preeclampsia - Bounds, Kelsey R.; Newell-Rogers, M. Karen; Mitchell, Brett M. (Frontiers in Cardiovascular Medicine, 2015)
The maternal innate immune system plays an important role both in normal pregnancy as well as hypertensive disorders of pregnancy including preeclampsia (PE). We propose 4 pathways that involve excessive innate immunity that lead to most forms of PE. Pre-existing endothelial dysfunction plus pregnancy leads to an excessive innate immune response resulting in widespread inflammation, placental and renal dysfunction, vasoconstriction, and PE. Placental dysfunction due to shallow trophoblast invasion, inadequate spiral artery remodeling, and/or low placental perfusion initiates an innate immune response leading to excessive inflammation, endothelial and renal dysfunction, and PE. A heightened innate immune system due to pre-existing or acquired infections plus the presence of a paternally-derived placenta and semi-allogeneic fetus cause an excessive innate immune response which manifests as PE. Lastly, an abnormal and excessive maternal immune response to pregnancy leads to widespread inflammation, organ dysfunction, and PE. We discuss the potential role of innate immunity in each of these scenarios, as well as the overlap, and how targeting the innate immune system might lead to therapies for the treatment of PE.